IMPLEMENTATION OF FARMING ACTIVITIES TO GROW CHILDREN'S NATURAL INTELLIGENCE - Meilani Nuris Salimah; Rika Wulandari; Kusnaningsih Kusnaningsih (maktab: Jurnal Pendidikan dan Teknologi, 2022)
One of the characteristics of elementary school students is that they like to play and get dirty. These characteristics can be taken into consideration to choose the right method of learning activities. This study aims to determine the relationship between farming activities and the naturalist intelligence of elementary school students. Naturalist intelligence is one of the 9 types of intelligence according to Gardner. The data collection method in this study was carried out by means of field observations and literature searches. As a result, farming activities are very suitable for elementary school children who basically like to play and get dirty. These activities will certainly make children more enthusiastic, active, and interactive. This makes learning more well-received by children when interspersed with direct practice such as farming. In addition, farming skills in children are able to stimulate cognitive aspects of children, especially about the types of plants about the parts of plants, get to know what things plants need to live, for example water, soil, sunlight, and so on. Knowledge of flora and how to plant and care for it will be able to shape children into individuals who are full of compassion for other living things. Thus, the application of farming is good in increasing children's naturalist intelligence